KOMUNIKASI NONVERBAL PADA BUSANA SANTRI - Lerry Calista Samty; Wisri (Fakultas Dakwah Universitas Ibrahimy, 2020)
Nonverbal communication is messages in the form of gestures, attitudes, faci facial expressions, symbolic clothing, sounds, and other symbol symbols that contain meaning. Signs of nonverbal communication have not been fully identified, but the results of the study show that how to sit, walk, dress, all that convey information to others. The purpose of this study was to find out the meaning of clothing for female students at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School. The method used in this study is a qualitative research method using semiotic analysis. Based on the findings in the field, it was found that the meaning of clothing for female santri was a necessity in a limited place, some also interpreted clothing as an interest that must be fulfilled. In addition, female students in the pesantren dress to reveal certain intentions and objectives and to convey messages nonverbally. Therefore the clothes worn by female students can influence the social interactions of fellow santri and communicate their lifestyle. This happened because the majority of female students were teenagers who naturally wanted to be recognized as a marker of self-identity.